INEXTENSIBLE FLOWS OF CURVES IN THE EQUIFORM GEOMETRY OF 4-DIMENSIONAL GALILEAN SPACE G4 - Bozok, Hulya Gun; Oztekin, Handan (Univ Nis, 2015)
In this paper, inextensible flows of curves in the equiform geometry of Galilean space G(4) are investigated. Necessary and sufficient conditions for inextensible flows of curves are expressed as a partial differential equation involving the equiform curvature in a 4-dimensional Galilean space G(4).
Keywords: Differential Geometry